2013
DOI: 10.1080/07448481.2013.824454
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Spiritual Well-Being and Health-Related Quality of Life in College Students

Abstract: SWB made a significant contribution to HRQL in a sample of college students. Such a relationship should be considered by campus health program planners to improve the quality of life of young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…The data also indicated that most participants (76%) depended on their faith when they became stressed. This data corresponded to Anye et al (2013) who found the more spiritual the student was, it resulted in higher scores in their satisfaction of feeling mentally and physically healthy. Also, 75.8% of participants believed that everything is going to be "okay" when they were stressed.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…The data also indicated that most participants (76%) depended on their faith when they became stressed. This data corresponded to Anye et al (2013) who found the more spiritual the student was, it resulted in higher scores in their satisfaction of feeling mentally and physically healthy. Also, 75.8% of participants believed that everything is going to be "okay" when they were stressed.…”
Section: Discussionsupporting
confidence: 69%
“…The more spiritual the student is, resulted in higher scores in regards to satisfaction of feeling mentally and physically healthy. Students who were not spiritually involved scored lower on the well-being scale (Anye et al, 2013). In regards to mental health, Mahmound, Staten, Hall, and Lennie (2012) found that whenever college students had a support system or a religious affiliation, it helped decrease their levels of stress.…”
Section: Spiritual Well-being and Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…A covariation of both was found with those with high rates of psychological well-being reporting beter health-related quality of life compared to those who reported a moderate sense of psychological well-being [30]. It has been recently found that a person's subjective perception of their own well-being greatly inluences HRQL, suggesting that by increasing people's perceptions we can help them atain higher levels of health-related quality of life [31], as well as beter quality of life during childhood and adolescence [32].…”
Section: Theoretical Frameworkmentioning
confidence: 90%